Analisa Pengaruh Persepsi Risiko Dan Kualitas Layanan Terhadap Niat Berkunjung Ulang Melalui Kepuasan Pasien Rawat Jalan (Studi Pada Instalasi Rawat Jalan Rsud dR. Sayidiman Magetan) - Emy Indriaswati; Yessy Artanti; Sri Setyo Iriani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Currently, the development of the health world is very rapid because it is supported by technological developments that can be used in an effort to improve hospital performance that improves the quality and safety of patients. Health facilities, both private and government, must always make the right strategy and continue to move in order to survive in the face of competition, and must be able to arouse the hearts of potential buyers to be able to make purchase intentions. This study aims to explain and analyze the influence of risk perception, service quality on revisit intention through outpatient satisfaction (Study on outpatient installation of dr. Sayidiman Hospital). This study uses a non-probability sampling technique. This type of research uses a quantitative descriptive method, by contacting a total of 140 respondents through online questionnaires/googleform and offline. The data was analyzed using the SEM (Structural Equation Model) PLS 3.0 technique. The findings of this study show that there is no positive effect between risk perception on revisit intention and patient satisfaction, but there is a positive influence on service quality and patient satisfaction on revisit intention. The results of this study are expected to be able to improve the quality of service and reduce the level of risk for patients in the outpatient installation of dr. Sayidiman Hospital.